Man-Made Ecology of East Kazakhstan - Bayandinova, Sairan (Environmental Science,, 2018)
This book highlights studies of differentiation problems of natural geosystems because of anthropogenic impact. The systematic methodology of comprehensive ecological assessment of anthropogenic impact on natural geosystems and their differentiations on the level of technogenic conditionality for ensuring rational environmental management and environmental protection are discussed. The practical importance of this book lies in the evidence-based recommendations and actions for conservation and quality management of the environment in order to decrease the degree of anthropogenic impact and in prevention of degradation processes. The book is useful to the researchers, industrial, scientific, and other organizations in establishing the purpose of the problem and solution to environmental protection and rational environmental management.